Suruacá. Experiência social e comunicação numa comunidade amazônica - CASTRO, Fábio Fonseca de (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
The paper discuss the significance of the idea of "communication" in an amazonian riverside community. Working with a hermeneutic perspective and the ethnographic method, it explores this sense from the social experience of the community. There is a topological central axis formed by the association between the ideas of community, organization and communication. With support from Simmel's understanding of the social forms and asymmetries, we propose that, in the observed community, communication is a form of meaning to those two contentes, community and organization and thus this topological axis conforms a language, a tool for mediation the asymmetry between the endogenous (the inhabitants of the community) and exogenous (an NGO and the Catholic Church, in its actions that place).